Approaches to automated construction of graphical shells for computer algebra systems - Alexander Colesnicov; Svetlana Cojocaru; Ludmila Malahova (Computer Science Journal of Moldova, 2008)
The paper proposes a calculator model of the graphical shell to be used for computer algebra systems. The calculator shell model is described. Then the techniques of semi-automated construction of such shell are discussed. The motivation of the approach based on the domain model is given. We describe also two possible component assembly methods, static and dynamic, and our experience with them. We motivate the selection of dynamic component assembly.